2020
DOI: 10.1021/acssuschemeng.0c06609
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Lepidolite from Tantalum–Niobium Mine Tailings by a Combined Magnetic–Flotation Process Using a Novel Gemini Surfactant: From Tailings Dams to the “Bling” Raw Material of Lithium

Abstract: On January 25, 2019, the tailings dam at Vale's Coŕrego do Feijao mine (Brumadinho, Minas Gerais, Brazil) ruptured, releasing about 12 million cubic meters of tailings, killing over 240 people and posing a considerable and ongoing environmental hazard. Thus, the recovery of valuable minerals from tailings can contribute to a sustainable disposal of this hazardous residue, saving human lives and protecting the environment. The tailings of a tantalum−niobium mine usually contain a considerable amount of lepidol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 41 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Of note, DDAC is a Gemini-type surfactant that has stronger adsorption on the target mineral surface, more activity and foaming power, a lower Krafft point, and improved foaming performance compared to traditional surfactants containing a single hydrophobic chain and a single polar group. Huang et al found that the novel Geminitype collector butanediyl-α,ω-bis(dimethyldodecylammonium bromide) (BBD) displayed a stronger low-temperature flotation performance than DDA [80]. Ni et al synthesized a new Gemini-type surfactant, hexane-1,6-didodecyldimethylammonium bromide (HDDA), which achieved selective separation of scheelite and calcite in pure mineral experiments without any inhibitors.…”
Section: Cationic Collectorsmentioning
confidence: 99%
“…Of note, DDAC is a Gemini-type surfactant that has stronger adsorption on the target mineral surface, more activity and foaming power, a lower Krafft point, and improved foaming performance compared to traditional surfactants containing a single hydrophobic chain and a single polar group. Huang et al found that the novel Geminitype collector butanediyl-α,ω-bis(dimethyldodecylammonium bromide) (BBD) displayed a stronger low-temperature flotation performance than DDA [80]. Ni et al synthesized a new Gemini-type surfactant, hexane-1,6-didodecyldimethylammonium bromide (HDDA), which achieved selective separation of scheelite and calcite in pure mineral experiments without any inhibitors.…”
Section: Cationic Collectorsmentioning
confidence: 99%
“…For example, one study uses desulfurization flotation techniques to separate sulfur-rich streams (Broadhurst et al, 2015) and generate by-products while simultaneously decreasing acid mine drainage potential. Another study relies on a combined magneticflotation, which can further improve technical performances and extract metals (Huang et al, 2020), and reduce the need for primary mining. If metal contents are high (< 0.5%-wt in copper tailings), other researchers encourage leaching or other separation techniques to maximize metal recoveries (X.…”
Section: Introductionmentioning
confidence: 99%
“…Mining is one of the major causes of metal contamination in water. Advances in the reverse floatation of mine tailings have been shown to alleviate soil and water pollution. Mercury is the most toxic element among the heavy metals, and the remediation of mercury-contaminated water and soil is very important. Other heavy-metal pollutants such as zinc, copper, lead, cadmium, chromium, and nickel, commonly found in the wastewater of electroplating, steel smelting, and paint manufacturing industries, are also threats to the environment and health. Gallium and indium compounds are extensively used in semiconductors. Moreover, the waste generated from gallium and indium compounds from the semiconductor industries is becoming a significant environmental issue due to the increasing demand for these products across the globe. , Methods to remove heavy metals from wastewater include chemical precipitation, ion exchange, adsorption, reverse osmosis, electrodialysis, and ultrafiltration. ,, Adsorption is one of the most effective methods to remove heavy metals since the process is relatively straightforward, low in cost, and highly efficient, whereas other removal techniques may have problems such as the generation of a large amount of sludge and costly disposal.…”
Section: Introductionmentioning
confidence: 99%